Multistakeholder knowledge levels and perspectives of human papillomavirus and its vaccination: An exploratory qualitative study. (7th October 2021) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Lee, Vivian Wing Yan; Lui, Grace Chun Yan; Butt, Laveeza; Chan, Kam Ming; Kwok, Chiu Yin; Lau, Alexander Yuk Lun
Abstract: Objective: This qualitative study was an integral part in the development of a multidisciplinary team‐led school‐based human papillomavirus vaccination health‐promotion programme (MDL‐SHPVP) aiming to increase HPV vaccine uptake in Hong Kong. Study findings will inform the design of the MDL‐SHPVP by drawing on interview data regarding the expectations and needs of key stakeholders and potential programme users. Methods: Eight mother–daughter dyads, four secondary school teachers, two school principals, three social workers and one school nurse were interviewed. All interviews were audio‐recorded and transcribed verbatim for thematic analysis. Results: Most participants had misconceptions about HPV and the vaccine. Alhough there was no immediate perceived need for the vaccination, most participants had favourable attitudes towards HPV inoculation and vaccines in general. Factors affecting vaccine uptake included perceptions about risk of infection, vaccine availability, and cost. Participants were largely open to suggested MDL‐SHPVP components (videos, digital game, and group discussions). Conclusion: Findings have highlighted knowledge gaps among potential users and key stakeholders and will be used to inform the design of the MDL‐SHPVP to ensure that their needs and expectations are addressed. Study findings may also aid future HPV vaccine promotion efforts and boost HPV vaccine uptake among youth in the city.